2020
DOI: 10.2147/eb.s277760
|View full text |Cite
|
Sign up to set email alerts
|

<p>Neuro-ophthalmic Complications of Immune Checkpoint Inhibitors: A Systematic Review</p>

Abstract: Objective Immune checkpoint inhibitors (ICIs) are novel cancer therapies that may be associated with immune-related adverse events (IRAEs) and come to the attention of neuro-ophthalmologists. This systematic review aims to synthesize the reported ICI-associated IRAEs relevant to neuro-ophthalmologists to help in the diagnosis and management of these conditions. Methods A systematic review of the literature indexed by MEDLINE, Embase, CENTRAL, and Web of Science database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 136 publications
0
43
0
Order By: Relevance
“…Although sintilimab has shown a potent efficacy in the treatment of tumors with manageable toxicity profiles, the side effects of sintilimab, including pneumonitis, anemia, diarrhea, colitis, hepatitis, nephritis, endocrinologic, hematologic, dermatologic, and other irAEs are inescapable ( 13 , 19 , 26 ). As the usage of sintilimab increases, some rare side effects have been documented, among them being neuro-ophthalmic complications of ICIs ( 12 , 19 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sintilimab has shown a potent efficacy in the treatment of tumors with manageable toxicity profiles, the side effects of sintilimab, including pneumonitis, anemia, diarrhea, colitis, hepatitis, nephritis, endocrinologic, hematologic, dermatologic, and other irAEs are inescapable ( 13 , 19 , 26 ). As the usage of sintilimab increases, some rare side effects have been documented, among them being neuro-ophthalmic complications of ICIs ( 12 , 19 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relatively rare ophthalmic irAEs have been only reported in less than 5% of patients treated with anti-PD-1 antibody-containing regimens ( 15 ). The optic neuritis was the fifth most common ICI-related ocular adverse event in lung cancer, and most of the patients with ocular irAEs other than ophthalmoplegia could be relieved after drug withdrawal and glucocorticoid treatment ( 17 , 27 ). Optic neuritis is one of the ophthalmic emergencies and may lead to permanent vision damage if left inappropriately treated ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cases of optic neuritis as an adverse event of immune checkpoint inhibitor (ICI) ingestion have also been reported, most commonly with ipilimumab, a CTLA-4 inhibitor. Further, ICIs such as PD-1 inhibitors (nivolumab and pembrolizumab) and PD-L1 inhibitors (atezolizumab or durvalumab) might cause optic neuropathy [ 123 , 124 ].…”
Section: Optic Neuropathy Induced By Toxic Substancesmentioning
confidence: 99%
“…Combination therapy results in the highest incidence of adverse events, and is typically higher with the CTLA4 inhibitor ipilimumab (138). In terms of ophthalmic complications, however, a recent systematic review identified pembrolizumab as the most common cause of a neuro-ophthalmic complication (32.1%) (139).…”
Section: Ocular Manifestations Secondary To Therapeutic Agentsmentioning
confidence: 99%